2016
DOI: 10.21037/jovs.2016.08.08
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal video-assisted thoracoscopic anatomic segmentectomy for small-sized lung cancer

Abstract: Increasing evidences prove video-assisted thoracic surgery (VATS) segmentectomy is accepted as a valid alternative to lobectomy esp. a greater number of small lung nodules have been detected.Uniportal VATS segmentectomy for small-sized lung cancer is more challenging not only for technical issues in simple or complex uniportal segmentectomy, but also considering oncological efficacy in terms of localization, safe margin, the extent of lymph node dissection and pathological analysis. In this work, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There are several recommendations to ensure the safe enough margins: Ginsberg and Rubenstein suggested the extension ≥ of 2 cm or margin-to-tumor ratio ≥1 (18), while Giraud et al concluded the extension <8 and <6 mm for adenocarcinoma and squamous carcinoma respectively (19). In Wang's segmentectomy series, segmental line always 3-5cm beyond which is spacious enough (20). Finally, according to the NCCN guideline, segmentectomy should achieve parenchymal resection margins ≥2 cm or ≥ the size of the nodule.…”
Section: Discussion Of Resection Margins and Lns Biopsymentioning
confidence: 99%
“…There are several recommendations to ensure the safe enough margins: Ginsberg and Rubenstein suggested the extension ≥ of 2 cm or margin-to-tumor ratio ≥1 (18), while Giraud et al concluded the extension <8 and <6 mm for adenocarcinoma and squamous carcinoma respectively (19). In Wang's segmentectomy series, segmental line always 3-5cm beyond which is spacious enough (20). Finally, according to the NCCN guideline, segmentectomy should achieve parenchymal resection margins ≥2 cm or ≥ the size of the nodule.…”
Section: Discussion Of Resection Margins and Lns Biopsymentioning
confidence: 99%
“…Single or combined basal segmentectomy (CBS), excluding common basal segmentectomy, is the most difficult of all types of segmentectomies due to the deeper location of the hilar structures, more structural variation, and more complex intersegmental plane adjacencies. Currently, only a few studies ( 7 , 8 ) have reported on thoracoscopic anatomical basal segmentectomy, and few studies have reported on the uniport approach ( 9 ). We previously published the largest case series on basal segmentectomy ( 10 ) with single-direction lobectomy ( 11 ) and we gradually began exploring uniport thoracoscopic basal segmentectomy (UTBS) and had good results ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of VATS segmentectomy have mainly focused on posterior, superior, dorsal, basal, and lingular segmentectomy . Lingulectomy is performed with left S4 + S5 segmentectomy.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Studies of VATS segmentectomy have mainly focused on posterior, superior, dorsal, basal, and lingular segmentectomy. [6][7][8] Lingulectomy is performed with left S4 + S5 segmentectomy. To the best of our knowledge, left S4 segmentectomy alone has never been reported.…”
Section: Introductionmentioning
confidence: 99%